2020
DOI: 10.24252/kesehatan.v1i1.16311
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Intervensi Brisk Walking: Literature Review

Abstract: Penyakit Tidak Menular (PTM) atau dikenal dengan Non Communicable Disease (NCD) semakin menjadi beban kesehatan, pembangunan ekonomi dan kesejahteraan sebagian besar populasi masyarakat saat ini (WHO, 2017). NCD merupakan penyebab utama kematian di tingkat global (2). Hal ini menyebabkan NCD menjadi salah satu tantangan utama Sustainable Development Goals (SDGs) dengan mengurangi kematian dini akibat NCD (3). Beberapa penyakit yang umum pada NCD adalah penyakit kardiovaskuler, diabetes mellitus, kanker dan pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Brisk walking was scientifically proven effective and easily promoted physical activity. Several studies showed that brisk walking has various health benefits, include effective in controlling blood sugar levels, improving and controlling the risk of being overweight or obese, and increasing muscle strength [26]. Physical activity could help people with diabetes improve fitness and strength, improve glycemic control, decrease insulin resistance, maintain weight loss, and reduce blood pressure.…”
Section: The Effect Of Brisk Walking On Blood Sugar Levelsmentioning
confidence: 99%
“…Brisk walking was scientifically proven effective and easily promoted physical activity. Several studies showed that brisk walking has various health benefits, include effective in controlling blood sugar levels, improving and controlling the risk of being overweight or obese, and increasing muscle strength [26]. Physical activity could help people with diabetes improve fitness and strength, improve glycemic control, decrease insulin resistance, maintain weight loss, and reduce blood pressure.…”
Section: The Effect Of Brisk Walking On Blood Sugar Levelsmentioning
confidence: 99%